INTEGRATED EDUCATION MANAGEMENT MODEL: A COMPARATIVE STUDY OF QUALITY IN STATE SCHOOLS AND INTEGRATED ISLAMIC SCHOOLS IN LUBUKLINGGAU CITY, SOUTH SUMATERA - Onky Paramanda Arma; Siti Inganah (RADJA PUBLIKA, 2025)
The development of education in Indonesia presents various models of educational institutions that differ in their management patterns and quality achievements. This study aims to analyze descriptively the education management model in state schools and Integrated Islamic Schools (IT) in Lubuklinggau City, and to examine its implications for the quality of education. The approach used is qualitative descriptive through literature study methods and analysis of related education policies. The results of the study indicate that state schools adopt more centralized administrative management models that prioritize national standards, while IT schools develop management models based on Islamic values ​​with a participatory approach and integrative curriculum. The differences in management models have an impact on quality aspects, such as academic achievement, character building, learning innovation, and stakeholder involvement. This study provides recommendations for the need for synergy of adaptive, contextual, and value-based management models in order to improve the quality of education in both types of schools.